Microbial interventions in yak colibacillosis: Lactobacillus-mediated regulation of intestinal barrier - Zhang, Jingbo; Ren, Xiaoli; Wang, Shuo; Liu, Ruidong; Shi, Bin; Dong, Hailong; Wu, Qingxia (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The etiology of Escherichia coli in yaks, along with its drug resistance, results in economic losses within the yak breeding industry. The utilization of lactic acid bacteria treatment has emerged as a viable alternative to antibiotics in managing colibacillosis. Methods To elucidate the therapeutic mechanisms of Lactobacillus against Escherichia coli-induced intestinal barrier damage in yaks, we employed yak epithelial cells as the experimental model and established a monolayer epithelial barrier using Transwell. The study encompassed four groups: a control group, a model group (exposed to E. coli O78), a low-dose Lactobacillus group (E. coli O78 + 1 × 105CFU LAB), and a high-dose Lactobacillus group (E. coli O78 + 1 × 107CFU LAB). Various techniques, including transmembrane resistance measurement, CFU counting, RT-qPCR, and Western Blot, were employed to assess indicators related to cell barrier permeability and tight junction integrity. Results In the Model group, Escherichia coli O78 significantly compromised the permeability and tight junction integrity of the yak epithelial barrier. It resulted in decreased transmembrane resistance, elevated FD4 flux, and bacterial translocation. Furthermore, it downregulated the mRNA and protein expression of MUC2, Occludin, and ZO-1, while upregulating the mRNA expression and protein expression of FABP2 and Zonulin, thereby impairing intestinal barrier function. Contrastingly, Lactobacillus exhibited a remarkable protective effect. It substantially increased transmembrane resistance, mitigated FD4 flux, and reduced bacterial translocation. Moreover, it significantly upregulated the mRNA and protein expression of MUC2, Occludin, and ZO-1, while downregulating the mRNA and protein expression of FABP2 and Zonulin. Notably, high-dose LAB demonstrated superior regulatory effects compared to the low-dose LAB group. Discussion In conclusion, our findings suggest that Lactobacillus holds promise in treating yak colibacillosis by enhancing mucin and tight junction protein expression. Furthermore, we propose that Lactobacillus achieves these effects through the regulation of Zonulin.